Book review: Living inside and against. Coloniality and decoloniality of power, 2022 - Germaná, César (2023)
Of the various issues raised by reading the book, two that are considered fundamental are examined: first, the problem of exposition, that is, the way in which Quijano presents the examination of complex problems; secondly, the exploration of the treatment of the problem of the decoloniality of power. The comment is concluded by pointing out Quijano’s interest in “the reconstitution of a Latin American problems”.